2019
DOI: 10.1016/j.resourpol.2019.01.019
|View full text |Cite
|
Sign up to set email alerts
|

Importance of oil shocks and the GCC macroeconomy: A structural VAR analysis

Abstract: This study is an endeavour to analyze the influence of oil price shocks on the macroeconomy of the Gulf Cooperation Council (GCC) member countries (Bahrain, Kuwait, KSA, Oman, Qatar and UAE). By employing a structural Vector auto-regression (SVAR) model for period 1980-2016, our key findings suggest that there are significant positive effects of oil price shocks on the GDP, inflation and trade balance of those countries. The findings, however, show substantial heterogeneities in the responses of the GCC member… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
40
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 109 publications
(42 citation statements)
references
References 72 publications
2
40
0
Order By: Relevance
“…To estimate this relationship, it will adopt the K variable panel structural VAR. Following the method explained by Lütkepohl, (2005), and Nasir, et al (2019), the panel SVAR specification starts with the VAR Model for the panel data, as follows:…”
Section: Methodsmentioning
confidence: 99%
“…To estimate this relationship, it will adopt the K variable panel structural VAR. Following the method explained by Lütkepohl, (2005), and Nasir, et al (2019), the panel SVAR specification starts with the VAR Model for the panel data, as follows:…”
Section: Methodsmentioning
confidence: 99%
“…Using a structural VAR model for the period 1980-2016, Nasir et al (2019) conclude the presence of significant heterogeneity in the reaction of GDP to oil shocks in GCC countries in terms of intensity, persistence, and duration. The authors confirm the existence of significant effects of oil shocks on GDP, inflation, and the trade balance.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Most empirical studies have debated the issue mentioned above in net oilimporting countries, specifically United States, Japan and the European Union (among others Hamilton, 2003;Zhang, 2008;Hanabusa, 2009;Das et al, 2018;Dagoumas et al, 2020). However, a review of the existing literature shows that there have been relatively limited studies analyzing the oil price-economic performance relationship in oil-exporting countries (Iwayemi & Fowowe, 2011;Nusair, 2016;Nasir et al, 2019;Charfeddine & Barkat, 2020), which represents a critical gap in the existing literature.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In their study to determine the causality relationship between oil prices volatility and economic growth for the period 1970–2002 in Ghana, Awunyo-Vitor et al (2018) found that the impact of the change in oil prices on economic growth in the long-run is statistically insignificant and there is a one-way causality relationship from the change in oil prices to economic growth. In another study of the Gulf Arab Countries Cooperation Council (GCC) countries (Bahrain, Qatar, Kuwait, Oman, Saudi Arabia, and the United Arab Emirates) with the data of 1980–2016, Nasir et al (2019) observed that oil price shocks have a statistically significant and positive effect on economic growth, although the degree of influence varies from country to country. Similarly, Erdogan et al (2020b) conducted a new study for GCC countries with monthly data for the period 2007–2018 and the SVAR model and found out that volatility in oil prices negatively affects economic growth in most GCC countries.…”
Section: Literature Reviewmentioning
confidence: 99%